Mapping Earthquake Vulnerable Areas Based on Microtremor Measurements Near Kebumen City - Widyawarman, Danang; Sismanto, Sismanto; Purnama, Aditya Yoga (Malaysian Journal of Science, 2024)
Kebumen, a district in Central Java, is regarded as a risky location because of the possibility of earthquakes. The risk level of earthquake hazard was assessed using a microtremor experiment in 10 subdistricts surrounding Kebumen, Java Tengah, using the characteristic soil dynamic parameters. A total of 82 points were collected using a single station seismometer, which has three components. An HVSR analysis was performed on the data. This vulnerability map also considers social, infrastructure, and economic vulnerabilities. According to the results of the microtremor analysis, the dominating frequency range is between 0.62 and 5.26 Hz. The amplification values ranged from 1,16 to 10,61. The thickness of the sediment layer ranged from 0.56 to 83.46 m. The seismic map was merged with maps of social vulnerability, infrastructure, and economics. The risk of earthquakes in the Kebumen area can be classified into three categories. The Pejagoan and Klirong sub-districts had the lowest earthquake risk. The second category area has a medium earthquake risk and predominates the experimental area, whereas the third category area has a high earthquake risk and predominates the Sruweng subdistrict.